Microplastic study on (litopenaeus vannamei) cultivation enterprises on the east coast of aceh - Abdullah Abbas Muhammadar; Ramadhan Furqan; Agustina Sri (BIO Web of Conferences, 2024)
Microplastics are small plastics measuring <5mm which, if they enter the water, can contaminate aquatic biota such as shrimp. The research aims to identify the number, shape and color of microplastics in shrimp bodies in vanname shrimp cultivation businesses on the East Coast of Aceh. Shrimp samples were taken from 3 stations, namely Pidie, Pidie Jaya and Bireuen. The samples were measured for weight and length, then prepared using H2O2 and H2SO4 in a ratio of 3:1 20 mL then incubated, heated, then filtered and identified using a Zeiss microscope with 40x magnification. The results obtained from shrimp body samples contained 2 types of microplastics, namely fiber and film. The most dominant microplastics at the three stations were 13 particles in the Pidie location, 9 particles in the Pidie Jaya location and 5 microplastic particles in the Bireuen location. The presence of microplastics that have entered the body of biota in the vannamei shrimp cultivation business is an early warning. So it is necessary to develop research on other consumption biota to determine the presence of microplastics and their impact if consumed by the public.